Cytotoxicity of Anti-VEGF Agents: An Experimental Study on ARPE-19 Cell Culture - Emir, Shergiye Bayramova; Ucgun, Nil Irem; Fikret, Cenk Zeki (Archives of Clinical and Biomedical Research, 2022)
Purpose: To determine the dose-related cytotoxic and oxidative stress effects of aflibercept, ranibizumab, bevacizumab on human retinal pigment epithelial cell (ARPE-19) culture. Study Design: Prospective, experimental. Material and Methods: ARPE-19 cells were inoculated into culture flasks with an appropriate medium mixture. Ranibizumab, Bevacizumab, and Aflibercept were added in clinical doses, twice clinical doses or four times of the clinical doses to the medium. ARPE-19 cell cultures without any anti- VEGF agents were used as the controls. The toxicity was evaluated with MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay in ARPE-19 cell cultures. Total antioxidant capacity (TAC) and Malondialdehyde (MDA) levels were measured by spectrophotometric method. Results: The cell viability was significantly lower than the control group at the clinical doses in Ranibizumab and Aflibercept groups, but not in the Bevacizumab group. Twice- and four times clinical doses resulted in significant cytotoxicity in all three anti-VEGF groups. The TAC levels were similar in all anti-VEGF and control groups. MDA level was significantly higher in all three anti-VEGF groups when compared to the control group. Conclusions: Aflibercept and ranibizumab, but not Bevacizumab reduced cell viability in ARPE-19 cell cultures at the clinical doses after 24 hours. Higher doses of all three agents caused cytotoxicity. Anti-VEGF agents did not change the TAC levels, however increased the MDA levels, and the cell toxicity after their application may be related to oxidative stress. It is wise to use anti-VEGF agents at minimum doses that provide maximum effectiveness with minimum cytotoxicity.